2008
DOI: 10.1002/icd.569
|View full text |Cite
|
Sign up to set email alerts
|

Parents' emotion‐related beliefs and behaviours in relation to children's coping with the 11 September 2001 terrorist attacks

Abstract: Parents have considerable impact on children's emotional lives. Parents are thought to model and inform children in myriad ways how to think about and feel emotion, and how to express and understand emotion in communication with others (Dix

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 70 publications
(68 reference statements)
5
64
1
4
Order By: Relevance
“…Though there has been little research on the parental belief that emotions can be dangerous, one study has demonstrated an association between parents’ belief that emotions can be dangerous and their children’s use of avoidance and distraction as ways of coping with their emotions following a set of terrorist attacks (Halberstadt, Thompson, Parker, & Dunsmore, in press). We chose to examine parents’ belief about the lack of acceptability or potential danger of children’s emotions because we expected this belief to relate to parents’ emotional experience.…”
Section: Parents’ Beliefs About Children’s Emotionsmentioning
confidence: 99%
“…Though there has been little research on the parental belief that emotions can be dangerous, one study has demonstrated an association between parents’ belief that emotions can be dangerous and their children’s use of avoidance and distraction as ways of coping with their emotions following a set of terrorist attacks (Halberstadt, Thompson, Parker, & Dunsmore, in press). We chose to examine parents’ belief about the lack of acceptability or potential danger of children’s emotions because we expected this belief to relate to parents’ emotional experience.…”
Section: Parents’ Beliefs About Children’s Emotionsmentioning
confidence: 99%
“…Nine items were used to assess participants' beliefs about the danger of negative emotions (see Appendix). The items were originally drawn from the Parents' Beliefs About Children's Emotions questionnaire (Halberstadt, Dunsmore et al, 2008, validated in Dunsmore et al, 2009Perez-Rivera & Dunsmore, 2011;Stelter & Halberstadt, 2011). Items were reworded as needed to address beliefs about emotions more generally outside of the parentÁchild relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work in the parenting literature highlights the role of emotion-related beliefs, which seem to act as overarching guides to behaviour. For instance, following the terrorist attacks of 11 September 2001, parents who reported strong beliefs about the danger of children's negative emotions reported engaging in longer discussions about the attacks with their children but also expressing less emotion in front of their children (Halberstadt, Thompson et al, 2008). In another study, parents who held less accepting beliefs about the value of children's expression and experience of negative emotions were more likely than those who did not to report non-supportive reactions to their children's negative emotions (Wong et al, 2009).…”
Section: Beliefs About Emotionsmentioning
confidence: 98%
See 1 more Smart Citation
“…There is no consensus for the interpretation of inter-rater agreement statistics, although the guidelines proposed by Landis and Koch (1977) often are used to define the level of agreement for the reported kappa. Studies which reported kappa statistics using data from their own sample include, among others, studies by Halberstadt et al (2008) for coding children’s coping strategies; Lutz et al (2007) for coding responses to the Child’s Reaction to Crisis Interview; Sprung (2008) for coding children’s unwanted intrusive thoughts; and Sprung and Harris (2010) for coding ratings of concentration and distractibility, cognitive cuing of emotions, and children’s unwanted intrusive thoughts. Kilmer et al (2009) reported a Kendall’s tau-b assessing reliability among raters of the Posttraumatic Growth Inventory for Children-Revised.…”
Section: Measurement and Instrumentationmentioning
confidence: 99%